Polya’s theorem and migration + capture of a quantum particle - Zagorodny А.G.; Christophorov, L.N. (Reports of the National Academy of Sciences of Ukraine, 2016)
Due to Polya's theorem, the quantum yield of capture of a particle, walking randomly on a low-dimensional lattice, by a trap located on one of its nodes is always 100 %, irrespective of the capture intensity. Under quantum migration, however, it is practically always less than 100 % and, contrary to intuition, only diminishes down to zero with the capture intensity growing.